Redemption through Resilience in Ian McEwan’s Atonement (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The scene by the fountain, its air of ugly threat, and at the end, when both hadgone their separate ways, the luminous absence shimmering above the wetnesson the gravel all this would have to be reconsidered.